2021
DOI: 10.1093/milmed/usab070
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effects of Burn Pit Exposure on the Respiratory Tract: A Systematic Review

Abstract: Introduction Burn pits (BPs) have been widely used by the U.S. military for waste disposal while in conflicts abroad. Significant adverse health effects are thought to be linked to BPs, but limited data exist examining the impact on the respiratory tract. The purpose of this systematic review is to characterize these effects on both the upper respiratory tract (URT) and lower respiratory tract (LRT). Materials and Methods A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…This limits the comparison of results with available data. However, airborne particles emitted during BMW incineration have also been found in other studies among air pollutants [15,[30][31][32].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This limits the comparison of results with available data. However, airborne particles emitted during BMW incineration have also been found in other studies among air pollutants [15,[30][31][32].…”
Section: Discussionsupporting
confidence: 54%
“…In Algeria, respiratory diseases are very frequent among steel workers, especially in the most polluted units, as well as among the inhabitants of the housing estate surrounding the plant [23]. Similarly, in a meta-analysis, the diagnosis of upper respiratory disorders appeared to increase as the exposure of the subjects to waste combustion pits increased [15]. Other authors found that short-term air pollution from traffic or organic carbon led to an increase in respiratory infection symptoms and emergency room visits by children [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to ultrafine particles generated from incomplete combustion of organic matter (e.g., cigarette smoke, burn pit, forest fire, and other environmental pollutants) causes lung inflammation and emphysema ( 6 , 36 ). We show that nCB fosters early and more invasive lung cancer in mice, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A newly published systematic review has highlighted an association between burn pit exposure and subjective pulmonary symptoms but was unable to link exposure with objective pulmonary findings 13 . To date, most burn pit–related research has focused on pulmonary diseases, specifically asthma, bronchitis, and deployment-related distal lung disease 14–17 .…”
mentioning
confidence: 99%